2018
DOI: 10.1093/ckj/sfy074
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D, bone alkaline phosphatase and parathyroid hormone in healthy subjects and haemodialysed patients from West Africa: impact of reference ranges and parathyroid hormone generation assays on the KDIGO guidelines

Abstract: Background The Kidney Disease: Improving Global Outcomes (KDIGO) guidelines recommend targets based on multiples of the upper limit of normal (ULN) of parathyroid hormone (PTH) concentration. However, the ULN has not always been correctly established by manufacturers. While it is known that the ULN is supposed to be higher in African Americans than in Caucasians, it is largely unknown in Africans. Methods We established the ULN of PTH concentration in a population of 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
0
8
2
2
Order By: Relevance
“…The authors found that bALP levels < 33.1 U/L discriminated low from non-low bone turnover and >42.1 U/L high from non-high turnover. Appropriate cut-off values using the Ostase mass bALP (IDS iSYS) have been suggested and include <21 µg/L for discriminating low from non-low bone turnover and >31 µg/L for high from non-high bone turnover [ 43 , 73 ].…”
Section: Assessment Of Bone Health In Ckd and Esrdmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors found that bALP levels < 33.1 U/L discriminated low from non-low bone turnover and >42.1 U/L high from non-high turnover. Appropriate cut-off values using the Ostase mass bALP (IDS iSYS) have been suggested and include <21 µg/L for discriminating low from non-low bone turnover and >31 µg/L for high from non-high bone turnover [ 43 , 73 ].…”
Section: Assessment Of Bone Health In Ckd and Esrdmentioning
confidence: 99%
“…Calcium and vitamin D supplements are often prescribed as adjuncts to osteoporosis treatment. Calcium supplementation is generally considered if dietary calcium is below 700 mg/day, and a calcium intake between 700 and 1200 mg is recommended [ 73 ]. In CKD, extra caution is advised because of impairment in calcium homoeostasis [ 93 ].…”
Section: Intervention For Fracture Reduction In Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma total intact PTH was measured by an electro-chemiluminescence immunoassay run. Based on the KDIGO recommendations [ 32 ]; Hyper-parathyroidism was defined as PTH >65 pg/mL or >6.89 pmol/L. Plasma Aldosterone levels, Plasma Angiotensin II levels and Plasma Renin activity were determined by ELISA assay kit (Isbio, Seattle, WA).…”
Section: Methodsmentioning
confidence: 99%
“…Cavalier et al . [7] explore another key issue: to what extent do biochemical thresholds generated in developed countries apply to other populations. They established the upper limit of normal of parathyroid hormone (PTH) concentration in healthy persons from the Ivory Coast and evaluated the prevalence of vitamin D deficiency, which was low.…”
mentioning
confidence: 99%